Translators and Social Context: The Case Study of Slovakia - Djovčoš, Martin (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2014)
This paper investigates the position of translators in Slovak society. It seeks an answer to the question who translates what, how and under which circumstances. To do so, it uses quantitative and qualitative methods of research. The quantitative analysis was performed with a questionnaire and data correlation analysis, whose results were then further tested via a qualitative analysis of 30 translations translated by 10 different translators (3 text types per each translator). The findings are juxtaposed with the ideas of Slovak and international translation scholars. The paper deals with translation as communication, the translation process, translator’s competences, the means by which these competences are acquired (formal education or practical experience) and how these factors influence the quality of translators’ output. This research paper presents results gained in the quantitative analysis.